2013
DOI: 10.1039/c3ra41196f
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive doped metals: high synergism in the bactericidal activity of chlorhexidine@silver towards wound pathogenic bacteria

Abstract: The entrapment of chlorhexidine (CH) within metallic silver (CH@Ag) results in a composite material bearing powerful synergetic bactericidal action towards two opportunistic wound pathogenic bacteria, the Gram-negative Pseudomonas aeruginosa and the Gram-positive Staphylococcus epidermidis. TEM and STEM imaging revealed morphological abnormalities in bacteria exposed to the composite. Release profiles of the active ingredients, CH and ionic silver, from the composite were evaluated by UV spectroscopy and by IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Hence, there is an urgent need for new approaches to overcome antibiotic resistance and to develop alternate antimicrobial agents that can control infectious diseases, the spread of pathogens and which have long-term effectiveness [3]. One area to prolong antimicrobial activity is with the incorporation of antimicrobial agents within sustained-release delivery systems for their continuous use [4][5][6]. The objective of using new sustained-release drug delivery systems is to enhance the therapeutic effectiveness of drugs, by decreasing their side effects and increasing their bioavailability in certain sites.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is an urgent need for new approaches to overcome antibiotic resistance and to develop alternate antimicrobial agents that can control infectious diseases, the spread of pathogens and which have long-term effectiveness [3]. One area to prolong antimicrobial activity is with the incorporation of antimicrobial agents within sustained-release delivery systems for their continuous use [4][5][6]. The objective of using new sustained-release drug delivery systems is to enhance the therapeutic effectiveness of drugs, by decreasing their side effects and increasing their bioavailability in certain sites.…”
Section: Introductionmentioning
confidence: 99%
“…13,[18][19][20] Importantly, the combination of CHX and Ag NPs has a synergistic antibacterial effect and improved biofilm inhibitory activity. 21,22 However, side effects occurring from the long-term coadministration without targeting the biofilm microenvironment may limit its further clinical applications. 23 In this regard, a promising drug co-delivery system is highly desirable for the controlled release of CHX and silver ions in response to a pathological environment in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Importantly, recent studies demonstrated that the combination of CHX and silver ions could engender an obviously synergistic bactericidal effect and improve the bactericidal efficacy. 17, 18 Monteiro et al 17 have demonstrated that silver nanoparticles (NPs) in combination with CHX may disrupt Candida biofilms, resulting in the prevention of resistance and improving the treatment of Candida-associated denture stomatitis. Ben-Knaz et al 18 fabricated…”
Section: Introductionmentioning
confidence: 99%
“…17, 18 Monteiro et al 17 have demonstrated that silver nanoparticles (NPs) in combination with CHX may disrupt Candida biofilms, resulting in the prevention of resistance and improving the treatment of Candida-associated denture stomatitis. Ben-Knaz et al 18 fabricated…”
Section: Introductionmentioning
confidence: 99%